KAJIAN DINAMIKA PENDUDUK KOTA PADANG (Jurnal Pelangi : Research of Education and Development, 2011)
The problem facing most countries in the world of high population growth,and including the state in Indonesia. This is due to the limited carryingcapacity of the earth to meet the needs human life. Space width did notknick the surface of the earth increases, while human needs are alwaysincreasing from year to year. This study aims to reveal, analyze, anddescribe about: 1) how much population growth Padang City , and 2) howis the dynamics of the population between 1990 and 2010 in Padang City.The results of this study can be concluded 1) Population growth in PadangCity overall has decreased even though the population continues to growfrom year to year. Ratio of population growth between 1990 and 2000amounted to 2.078%, while in 2000 until 2010 the ratio decreased to0.703%, and 2) Population growth in Padang City as a whole is stronglyinfluenced by the conditions of migration. Based on the last three censusperiods the average population growth in Padang City influenced bymigration, with percentage of 69.54% while the natural population growthonly affects the conditions of residence in Padang City is less than 40%.